Evidence for shock‐induced anhydrite recrystallization and decomposition at the UNAM‐7 drill core from the Chicxulub impact structure. (4th April 2019) - Salge, T.; Stosnach, H.; Rosatelli, G.; Hecht, L.; Reimold, W. U.
Abstract: Drill core UNAM‐7, obtained 126 km from the center of the Chicxulub impact structure, outside the crater rim, contains a sequence of 126.2 m suevitic, silicate melt‐rich breccia on top of a silicate melt‐poor breccia with anhydrite megablocks. Total reflection X‐ray fluorescence analysis of altered silicate melt particles of the suevitic breccia shows high concentrations of Br, Sr, Cl, and Cu, which may indicate hydrothermal reaction with sea water. Scanning electron microscopy and energy‐dispersive spectrometry reveal recrystallization of silicate components during annealing by superheated impact melt. At anhydrite clasts, recrystallization is represented by a sequence of comparatively large columnar, euhedral to subhedral anhydrite grains and smaller, polygonal to interlobate grains that progressively annealed deformation features. The presence of voids in anhydrite grains indicates SOx gas release during anhydrite decomposition. The silicate melt‐poor breccia contains carbonate and sulfate particles cemented in a microcrystalline matrix. The matrix is dominated by anhydrite, dolomite, and calcite, with minor celestine and feldspars. Calcite‐dominated inclusions in silicate melt with flow textures between recrystallized anhydrite and silicate melt suggest a former liquid state of these components. Vesicular and spherulitic calcite particles may indicate quenching of carbonate melts in the atmosphere at high cooling rates, and partial decomposition during decompression at postshock conditions. Dolomite particles with a recrystallization sequence of interlobate, polygonal, subhedral to euhedral microstructures may have been formed at a low cooling rate. We conclude that UNAM‐7 provides evidence for solid‐state recrystallization or melting and dissociation of sulfates during the Chicxulub impact event. The lack of anhydrite in the K‐Pg ejecta deposits and rare presence of anhydrite in crater suevites may indicate that sulfates were completely dissociated at high temperature ( T  > 1465 °C)—whereas ejecta deposited near the outer crater rim experienced postshock conditions that were less effective at dissociation.